USING BUZZ GROUP TECHNIQUE IN TEACHING READING COMPREHENSION TO THE TENTH GRADE STUDENTS OF SMA MUHAMMADIYAH PAGARALAM - Sri Wahyuni (Universitas PGRI Palembang, 2021)
The main problem of this research â€œwas there any significant difference in reading comprehension between students who were taught by using Buzz group technique and those who were not in the tenth graders of SMA Muhammadiyah Pagaralam?â€ The objective of this study was to find out whether or not there was any significant difference in reading comprehension between students who were taught by using Buzz group technique and those who were not in the tenth graders of SMA Muhammadiyah Pagaralam. The population of this researchÂ was all tenth grade students of SMA Muhammadiyah Pagaralam, consist ofÂ 259Â students. TwoÂ classes were chosen as the sample and they divided into experimental class and control class that consist of 32 students each classes. The sample were taken by using purposive sampling. Quasi experimental method was used in this research. The result of pre-test and post-test in experimental class and control class were compared by using independent sample t-test, in term of reading aspects. The value of t-obtained was 4,628, at the significance value p<0.05 in two tailed testing with df = 62, the critical value of the t-table was 1.999. Since the value of t-obtained was higher than the critical value of t-table, the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. It could be concluded that there was significance different in the studentsâ€™ reading comprehension in the experimental class at every aspect before and after treatment by using Buzz Group Technique.